2013
DOI: 10.1155/2013/398034
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Predicts All-Cause and Cardiac Mortality in Females with Suspected Acute Coronary Syndrome: A Comparison with Brain Natriuretic Peptide and High-Sensitivity C-Reactive Protein

Abstract: Vitamin D may not only reflect disease but may also serve as a prognostic indicator. Our aim was to assess the gender-specific utility of vitamin D measured as 25-hydroxy-vitamin D [25(OH)D] to predict all-cause and cardiac death in patients with suspected acute coronary syndrome (ACS) and to compare its prognostic utility to brain natriuretic peptide (BNP) and high-sensitivity C-reactive protein (hsCRP). Blood samples were harvested on admission in 982 patients. Forty percent were women (65.9 ± 12.6 years). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In fact, this is supported by several prospective studies where a low vitamin D level has been shown to predict a worse outcome and also a shorter life span in patients with several different cancer forms, including colorectal and renal cancer [ 26 – 29 ]. Moreover, several large meta-analyses have found that low vitamin D levels are associated with an increased overall mortality and also with death caused by cancer [ 14 , 15 , 30 ]. Thus, it is possible that vitamin D has a true effect on pain mechanisms in cancer patients and that the confounding effect of age, can be explained by the fact that patients with a high vitamin D level survive longer with their cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this is supported by several prospective studies where a low vitamin D level has been shown to predict a worse outcome and also a shorter life span in patients with several different cancer forms, including colorectal and renal cancer [ 26 – 29 ]. Moreover, several large meta-analyses have found that low vitamin D levels are associated with an increased overall mortality and also with death caused by cancer [ 14 , 15 , 30 ]. Thus, it is possible that vitamin D has a true effect on pain mechanisms in cancer patients and that the confounding effect of age, can be explained by the fact that patients with a high vitamin D level survive longer with their cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) show beneficial effects of vitamin supplementation against infections [ 11 13 ]. Moreover, observational studies have shown that low vitamin D-levels are associated with increased all-cause mortality [ 14 , 15 ]. In a meta-analysis of 159 RCTs it was shown that treatment with vitamin D 3 was associated with decreased mortality, and especially mortality caused by cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For future personalized diagnosis and prognosis in ACS and HF patients, a temporal multimarker approach could be employed to monitor the functions of different biological pathways over time. For example, markers for status of cardiac damage (hs-cTnI), markers for pathophysiological status (CRP and other cytokines), and markers for cardiac dysfunction (BNP) can be monitored over time as a multi-marker panel [ 56 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prognostic utility of vitamin D in relation to long-term CV outcomes has been evaluated in subjects without a history of CVD, as in the Framingham Offspring study [ 13 ] and in patients with established CVD [ 14 , 15 ]. We have previously shown that 2- and 5-year total and cardiac mortality is decreased in the highest as compared to the lowest quartile of vitamin D in a coronary chest-pain population living at altitudes exceeding 1000 meters in subtropical northern Argentina [ 16 ], and this relationship is stronger in females than in males [ 17 ].…”
Section: Introductionmentioning
confidence: 99%